ANALISIS PENDAPATAN PADI LOKAL VARITAS KARANGDUKUH (Oryza sativa L) DI KECAMATAN TAMBAN CATUR KABUPATEN KAPUAS - Achmad Jaelani; Ari Jumadi Kirnadi; Bagiyo Mujiono (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
The purpose of this research was to know the income and the value efficiency of Paddy Local Paddy Karangdukuh Variety (Oryza sativa L) In Tamban Catur Sub-district the Regency of Kapuas. The sample was taken randomly using Purpossive Random Sampling. There were 35 respondents from 4 village which each village put 10 farmers and one vilage put 5 farmers. The data collection was done by interviewing 35 local paddy farmers in Tamban Catur Sub-district becomes the respondents directly. The data needed for the research is premier data that taken directly from the research field and the secondary data was gotten from the library study, the related agency and other sources that relate to this research. The data was processed and analyzed using income analysis and R/C Ratio. Based on the observation result of 35 respondents, the farmers of local paddy Karangdukuh variety were using semi intensive farming, with the average total cost per respondent Rp7.341.981,- kg year-1 and the total revenue that gotten is Rp16.324.400, year-1. The obtained results local paddy farm income is Rp Rp11.243.522,- year-1. The value average R/C Ratio that gotten is 2.2 which means that the local paddy Karangdukuh variety is getting profit.